HUMAN RESOURCE DEVELOPMENT STRATEGY AND EDUCATIONAL MARKETING MIX IN IMPROVING THE COMPETITIVENESS OF EDUCATIONAL INSTITUTIONS: HUMAN RESOURCE DEVELOPMENT STRATEGY AND EDUCATIONAL MARKETING MIX IN IMPROVING THE COMPETITIVENESS OF EDUCATIONAL INSTITUTIONS - Maryati Marya; Aan Anengsih; Anis Zohriah; Abdul Mu’in (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze human resource development strategies and educational marketing mix in enhancing the competitiveness of Islamic educational institutions. The research method employed is qualitative with a case study approach on Islamic educational institutions in Indonesia. Data collection techniques were conducted through in-depth interviews, observations, and documentation studies. The results indicate that HR development through continuous training, digital competency enhancement, and strengthening Islamic values significantly influences the effectiveness of educational marketing mix implementation. Marketing mix strategies including product, price, place, promotion, people, process, and physical evidence can be optimized when supported by competent and professional human resources. The synergy between HR development and marketing mix has proven capable of increasing brand awareness, public trust, and student enrollment numbers. This study recommends the importance of continuous investment in marketing HR capacity development and integration of holistic marketing strategies to win competition in the digital era.